2021
DOI: 10.3846/btp.2021.12417
|View full text |Cite
|
Sign up to set email alerts
|

Young Generation and Environmental Friendly Awareness: Does It the Impact of Green Advertising?

Abstract: The environmental issues nowadays have make consumers becoming more selective in selecting products and brands going to use. The purpose of this study is to investigate the effect of green advertising on green purchase intentions mediated by green attitude awareness in the young generation. Young generation has strong curiosity and has easier access on getting products information, so this research focuses deeper on examining how much green advertising, green knowledge, and eco-label information affect the awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
3
2
0
1
Order By: Relevance
“…It supports the notion that GAD heightens consumer consciousness and stimulates their environmental awareness, thus encouraging the purchase of organic products [48,50]. This finding is in line with other research that has established a positive relationship between GAD and EAW [37,38,55,56,65,66] and challenges those studies which assert that GAD does not enhance the EAW of organic product consumers [13,61].…”
Section: Discussionsupporting
confidence: 89%
“…It supports the notion that GAD heightens consumer consciousness and stimulates their environmental awareness, thus encouraging the purchase of organic products [48,50]. This finding is in line with other research that has established a positive relationship between GAD and EAW [37,38,55,56,65,66] and challenges those studies which assert that GAD does not enhance the EAW of organic product consumers [13,61].…”
Section: Discussionsupporting
confidence: 89%
“…This supports the finding that the GAD raises consumer awareness and stimulates their environmental awareness to encourage them to purchase organic products [48,50]. This finding supports the results of other research that has identified a positive relationship between green advertising and environmental awareness [37,38,55,56,66,67] and contradicts the positions of research that has determined that GAD does not stimulate the EAW of consumers who consume organic products [13,61].…”
Section: Discussionsupporting
confidence: 81%
“…Based on the above discussion, it can be argued that airport authorities can adopt ADD, promoting EB through ATT. ADD and knowledge can significantly enhance EB through a better attitude toward environmental practices (Herman et al ., 2021; Kusuma and Handayani, 2018; Yusiana et al ., 2022).…”
Section: Hypothesis Developmentmentioning
confidence: 99%